The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1080/13510347.2018.1527316
|View full text |Cite
|
Sign up to set email alerts
|

Sharīʻa, Islamism and Arab support for democracy

Abstract: The Arab Spring and its aftermath reignited the debate over the relationship between Islamism and democracy. This analysis improves upon previous research by demonstrating the crucial contribution which a more precise understanding of the multiple meanings of the concept of Shar a can have on our assessment of the future of democracy in the Arab world.While support for the Shar a-conformity of laws has a positive impact on the preference for democracy, the insistence that Shar a represents the word of God as o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…By ‘secularism’, we mean the idea that ‘religion as a source of authority in social and intellectual questions is not privileged over other sources of authority in societies internally differentiated’ (Al-Azmeh, 2019: 8). Then, in Sunni-majority societies, secular political forces are those that oppose the deep effective translation of the above-mentioned narrow conception of sharī‘a into positive law (or at least its limitation to the realm of family law), even if they can express a generic support for the word sharī‘a (Berger, 2019) and accept its symbolic role in the Constitution (Blouët and Steuer, 2015). This is the case in Egypt, whose Constitution states in its Article 2 – since 1980 – that the principles of sharī‘a are the main source of law.…”
Section: Review Of Literature and Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…By ‘secularism’, we mean the idea that ‘religion as a source of authority in social and intellectual questions is not privileged over other sources of authority in societies internally differentiated’ (Al-Azmeh, 2019: 8). Then, in Sunni-majority societies, secular political forces are those that oppose the deep effective translation of the above-mentioned narrow conception of sharī‘a into positive law (or at least its limitation to the realm of family law), even if they can express a generic support for the word sharī‘a (Berger, 2019) and accept its symbolic role in the Constitution (Blouët and Steuer, 2015). This is the case in Egypt, whose Constitution states in its Article 2 – since 1980 – that the principles of sharī‘a are the main source of law.…”
Section: Review Of Literature and Definitionsmentioning
confidence: 99%
“…Consequently, all the Egyptian parties need to have at least some Christians and some women among their members. The issue is particularly critical for Islamist parties because the sharī‘a tends to elicit conflicts with gender equality and religious equality (Berger, 2019: 3–5). Yet, during the past half-century, many Islamist organizations have shifted from condemning women’s public presence to seeing women as agents of the Islamization and moralization of public life (Jad, 2018; Rock-Singer, 2019: 154–178).…”
Section: Review Of Literature and Definitionsmentioning
confidence: 99%
“…When a positive correlation between embracing Islam and violence does exist, the relationship is driven by a particular understanding or interpretation of Islam and the concomitant personal obligations they believe Islam establishes for Muslims (Haddad 2004; Fair et al 2012; Fair et al 2018a; Berger 2019).…”
Section: Drivers Of Individual Support For Islamist Violence: What Th...mentioning
confidence: 99%
“…Most of this work yielded null or inconclusive results. For example, a pooled analysis of data from 12 Arab countries suggested that, contrary to conventional wisdom, support for sharia laws increased support for democracy (Berger, 2019; the opposite effect was found for belief that sharia constitutes the word of God in this study), while other analyses of data from different samples of Arab countries showed that it is negatively associated with democratic support (Spierings, 2014) and with openness to diverse political ideas (Tessler, Jamal, & Robbins, 2012).…”
Section: The Religion‐democracy Puzzlementioning
confidence: 99%